Different renal phenotypes in related adult males with Fabry disease with the same classic genotype. Issue 4 (8th May 2017) - Mignani, Renzo; Moschella, Mariarita; Cenacchi, Giovanna; Donati, Ilaria; Flachi, Marta; Grimaldi, Daniela; Cerretani, Davide; Giovanni, Paola De; Montevecchi, Marcello; Rigotti, Angelo; Ravasio, Alessandro
Abstract: Background: Fabry disease related patients with classical mutation usually exhibit similar severe phenotype especially concerning renal manifestation. Methods: A dry blood spot screening (DBS) and the DNA analysis has been performed in a 48‐year‐old man (Patient 1) because of paresthesia. Results: The DBS revealed absent leukocyte α ‐Gal A enzyme activity while DNA analysis identified the I354K mutation. Serum creatinine and e‐GFR were in normal range and also albuminuria and proteinuria were absent. The brain MRI showed ischemic lesions and a diffuse focus of gliosis in the white matter, while the echocardiogram showed a left ventricular hypertrophy. The renal biopsy performed in the case index showed a massive deposition of zebra bodies. By a familiar investigation, it was recognized that his brother (Patient 2) died 2 years before from sudden death syndrome at the age of 49. He had suffered sporadic and undiagnosed pain at the extremities, a prior cataract, bilateral neurosensorial hearing loss and left ventricular hypertrophy on Echocardiogram. His previous laboratory examinations revealed a normal serum creatinine and the absence of proteinuria. Pedigree analysis of the brothers revealed a high disease burden among family members, with an affected cousin (Patient 3) who progressed early to end‐stage renal disease (ESRD) that required renal transplantation. Conclusions: Here we describe the clinical history of three adult male members of the same family with the same genotype who manifested different presentation and progression of the disease, particularly concerning the renal involvement. Abstract : Fabry disease‐related patients with classical mutation usually exhibit similar severe phenotype especially concerning renal manifestation In patient 1 DBS revealed absent leukocyte a‐Gal A enzyme activity while DNA analysis identified the I354K mutation. Serum creatinine and e‐GFR were in normal range and albuminuria/proteinuria was absent. By a familiar investigation, it was recognized that his brother (Patient 2) died 2 years ago from sudden death syndrome at the age of 49. His previous laboratory examinations revealed a normal serum creatinine and the absence of proteinuria. Pedigree analysis of the brothers revealed a high disease burden among family members, with an affected cousin (Patient 3) who progressed to early end‐stage renal disease (ESRD) that required renal transplantation.